An in vitro assessment of type, position and incidence of isthmus in human permanent molars - Fernando José Camello de LIMA; Francisco MONTAGNER; Rogério Castilho JACINTO; Glaucia Maria Bovi AMBROSANO; Brenda Paula Figueiredo de Almeida GOMES (University of São Paulo, 2014)
Root canal anatomical complexities, such as isthmus, may limit the action of the endodontic instruments, irrigant solutions and intracanal medications, leading to endodontic treatment failure. Objectives: This in vitro study assessed the type, position and incidence of isthmus in human permanent molars. Material and Methods: One hundred and twenty eight upper and lower first and second permanent molars were analyzed. The roots were embedded in transparent resin, and then split at different distances from the apex (1.0-2.5-4.0-5.5-7.0 mm). Following the sample examination in stereomicroscope, the data were submitted to chi-square statistical test at a 5% significance level. Results: The highest isthmus incidence was at 7.0 mm from the root apex in all samples, except the distal root of lower molars (at 5.5 mm). In upper and lower molars, type V (complete isthmus with a continuous opening between the two main root canals) was the most common classification of isthmus (28.8%). In the mesial root of first and second mandibular molars, type IV had the highest incidence (36% and 23.9%, respectively). Conclusion: It was concluded that isthmus was widely found in flat roots, with a low percentage in areas close to the apex. In upper and lower molars, these structures were most frequently found at 7 mm from the apex.